Logical Reasoning and Teaching Mathematical Statistics - Almaguer, Arisdorgan Diéguez; Saavedra, Hilter Farley Figueroa; Velasco, Aurora Azucena Ariza; Monier, Yoan Pablo Rodríguez; Álvarez, Kenichi Gaspar García (International Journal of Psychosocial Rehabilitation, 2020)
The article addresses general knowledge about constructivism, significant knowledge, metacognition and logical reasoning, which constitute the theoretical basis for the methodological development of an alternative teaching-learning process for Mathematical Statistics, in a meaningful and coherent way. To do this, it starts with elementary contents of Arithmetic and Geometry, as a representation on the number line and Pythagorean Theorem to induce the formulas of central tendency and dispersion measures and provide the student with tools for understanding the contents. This proposal helps the student to learn more easily, not only Mathematical Statistics, but also provides a method based on logical reasoning, where the cause-effect relationship is evidenced, from the simple to the complex, and the verification of the main phenomena, which is useful for coping with cognitive tasks in broader fields.